UTILIZATION OF TELEHEALTH IN MIDWIFERY SERVICES DURING THE COVID-19 PANDEMIC: A QUALITATIVE STUDY - Avina Oktaviani Algifnita; Ivon Diah Wittiarika (UNIVERSITAS AIRLANGGA, 2022)
Background: The COVID-19 pandemic has a significant impact on midwifery services, especially in Midwife Self-Practice. The government, Dinas Kesehatan, and professional organizations released many health protocols, urging all activities at home as well as regional restrictions to limit the spread of COVID-19. This leads to a slowdown in access to health services, especially midwifery. Telehealth services are recommended by the government and must be implemented in every health facility to strive to improve the quality of health. Midwives are one of the vanguards in and in maternal and child health services that can utilize telehealth in their services in Midwife Self-Practice during the COVID-19 pandemic. Objective: To analyze the influence of telehealth utilization in midwifery services during the COVID-19 Pandemic. Method: A qualitative phenomenology with data collection method through a semi-structured in-depth interview conducted in March-April 2021 at The Midwife Independent Practice in Surabaya. The study participants were midwives who owned The Independent Practice of Midwives using purposive sampling techniques. Result: During the COVID-19 pandemic, two themes were obtained, namely the utilization of telehealth and the influence of telehealth in obstetric services. Conclusion: Midwives believe that there is a positive influence in the use of telehealth, in addition to being profitable, it can also be used as an alternative in midwifery services during the COVID-19 pandemic. Keywords: Health Policy, Telehealth, Maternal Health, COVID-19